The Kelp Cultivation Potential in Coastal and Offshore Regions of Norway - Broch, Ole Jacob; Alver, Morten Omholt; Bekkby, Trine; Gundersen, Hege; Forbord, Silje; Handå, Aleksander; Skjermo, Jorunn; Hancke, Kasper (Frontiers in Marine Science, 2019)
We have evaluated the cultivation potential of sugar kelp (Saccharina latissima) as a function of latitude and position (near- and offshore) along the Norwegian coast using a coupled 3D hydrodynamic-biogeochemical-kelp model system (SINMOD) run for four growth seasons (2012–2016). The results are spatially explicit and may be used to compare the suitability of different regions for kelp cultivation, both inshore and offshore.The simulation results were compared with growth data from kelp cultivation experiments and in situ observations on coverage of naturally growing kelp. The model demonstrated a higher production potential offshore than in inshore regions, which is mainly due to the limitations in nutrient availability caused by the stratification found along the coast. However, suitable locations for kelp cultivation were also identified in areas with high vertical mixing close to the shore. The results indicate a latitudinal effect on the timing of the optimal period of growth, with the prime growth period being up to 2 months earlier in the south (58 °N) than in the north (71 °N). Although the maximum cultivation potential was similar in the six marine ecoregions in Norway (150–200 tons per hectare per year), the deployment time of the cultures seems to matter significantly in the south, but less so in the north. The results are discussed, focusing on their potential significance for optimized cultivation and to support decision making toward sustainable management.